2018
DOI: 10.1002/pc.25002
|View full text |Cite
|
Sign up to set email alerts
|

Examination of low‐velocity impact and mechanical properties after impact of fiber‐reinforced prepreg composites

Abstract: Fiber-reinforced prepreg composites are considered to be the most promising materials for aerospace applications. However, these composites are susceptible to impact during in-service phases. The impact can cause various types of damage, such as matrix cracks, delamination and fiber breakage, thereby considerably decreasing their mechanical properties. In this study, a series of experiments were carried out to investigate the LVI characteristics. The impact damage characteristics of the fiber-reinforced prepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The strength retention rates of the UC, SO, and LO specimens are 61.78%, 67.40%, and 67.56%, respectively, when the impact energy reaches 12 J. This implies that the discontinuous structure improves the residual properties of the materials under high impact energy 36 . Further, the strength retention rate of the LO specimen is larger than that of the SO specimen in all cases, which proves that the LO specimen has a better impact resistance than the SO specimen.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The strength retention rates of the UC, SO, and LO specimens are 61.78%, 67.40%, and 67.56%, respectively, when the impact energy reaches 12 J. This implies that the discontinuous structure improves the residual properties of the materials under high impact energy 36 . Further, the strength retention rate of the LO specimen is larger than that of the SO specimen in all cases, which proves that the LO specimen has a better impact resistance than the SO specimen.…”
Section: Resultsmentioning
confidence: 89%
“…This implies that the discontinuous structure improves the residual properties of the materials under high impact energy. 36 Further, the strength retention rate of the LO specimen is larger than that of the SO specimen in all cases, which proves that the LO specimen has a better impact resistance than the SO specimen. Further, this reveals that the damage tolerance of the LO specimen is slightly higher than that of the SO specimen.…”
Section: Damage Tolerance and Mode Of Discontinuous Laminatesmentioning
confidence: 77%
“…The LVI test results indicated that impact energy mainly affects the damage failure of composites. 34 Figure 2A displays the impact force-time and energy absorption-time curves of a typical LVI. The velocity of the impactor is calculated using Equation (1), where V (t), V i , F(t), m, and g represent the velocity of the impactor at a time "t," initial velocity, stress at a time "t," the mass of the impactor, and gravitational acceleration, respectively.…”
Section: Performance Testingmentioning
confidence: 99%
“…[1][2][3][4] For instance, low-velocity impact (LVI) is a major issue, and this type of damage can cause invisible damage to the material, such as matrix cracking, microcracking, and internal delamination. [5][6][7][8][9][10] In addition to affecting the structure's strength, durability, and stability, these defects are frequently difficult to detect and repair. Moreover, such inherent limitations lead to an increase in composite waste, which is certain to have a significant impact on the environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, CFRP still has weaknesses, including poor interlayer toughness due to the lack of z ‐directional toughening and a unique laminated structure that is susceptible to out‐of‐plane loads 1–4 . For instance, low‐velocity impact (LVI) is a major issue, and this type of damage can cause invisible damage to the material, such as matrix cracking, microcracking, and internal delamination 5–10 . In addition to affecting the structure's strength, durability, and stability, these defects are frequently difficult to detect and repair.…”
Section: Introductionmentioning
confidence: 99%